Collectives of humans-with-media in mathematics education: Notebooks, blackboards, calculators, computers and ... notebooks throughout 100 years of ICMI - Villarreal, Mónica E.; Borba, Marcelo C. [UNESP] (Springer Nature, 2010)
The main aim of this study was to present evidence of the ways in which different media have conditioned and dramatically reorganized education, in general, and mathematics education, in particular. After an introduction of the theme, we discuss the epistemological perspective that provides the foundation for our analysis: the notion of humans-with-media. Then, we briefly illustrate how the medium is related to the scientific production of mathematical knowledge. We take a detour into the world of art to examine how devices and instruments have historically been associated with the production of mathematical knowledge. Then, we review studies on the history of education to show how traditional media were introduced into schools and have influenced education. In particular, we examine how devices such as blackboards and notebooks, which were novelties a 100 years ago, came to be accepted in schools and the mathematical activities that were promoted with their use. Finally, we discuss how information technology has changed education and how the Internet may have an impact on mathematics education comparable to that of the notebook over a century ago. © FIZ Karlsruhe 2009.
Keywords: Blackboard; History of ICMI; Humans-with-media; Information and communication technology; Notebook; Textbook